Differential activity and selectivity of N‐terminal modified CXCL12 chemokines at the CXCR4 and ACKR3 receptors. Issue 6 (6th May 2020) - Jaracz‐Ros, Agnieszka; Bernadat, Guillaume; Cutolo, Pasquale; Gallego, Carmen; Gustavsson, Martin; Cecon, Erika; Baleux, Françoise; Kufareva, Irina; Handel, Tracy M.; Bachelerie, Françoise; Levoye, Angélique
Abstract: Chemokines play critical roles in numerous physiologic and pathologic processes through their action on seven‐transmembrane (TM) receptors. The N‐terminal domain of chemokines, which is a key determinant of signaling via its binding within a pocket formed by receptors' TM helices, can be the target of proteolytic processing. An illustrative case of this regulatory mechanism is the natural processing of CXCL12 that generates chemokine variants lacking the first two N‐terminal residues. Whereas such truncated variants behave as antagonists of CXCR4, the canonical G protein‐coupled receptor of CXCL12, they are agonists of the atypical chemokine receptor 3 (ACKR3/CXCR7), suggesting the implication of different structural determinants in the complexes formed between CXCL12 and its two receptors. Recent analyses have suggested that the CXCL12 N‐terminus first engages the TM helices of ACKR3 followed by the receptor N‐terminus wrapping around the chemokine core. Here we investigated the first stage of ACKR3‐CXCL12 interactions by comparing the activity of substituted or N‐terminally truncated variants of CXCL12 toward CXCR4 and ACKR3. We showed that modification of the first two N‐terminal residues of the chemokine (K1R or P2G) does not alter the ability of CXCL12 to activate ACKR3. Our results also identified the K1R variant as a G protein‐biased agonist of CXCR4. Comparative molecular dynamics simulations of the complexes formed by ACKR3 either with CXCL12 or with the P2G variant identified interactions between the N‐terminal 2–4 residues of CXCL12 and a pocket formed by receptor's TM helices 2, 6, and 7 as critical determinants for ACKR3 activation. Abstract : Two to four N‐terminal residues of CXCL12 are critical for binding to ACKR3 and required for activation of both CXCR4 and ACKR3.